IDENTIFYING STUDENTS' ABILITIES IN PRONUNCIATION OF WORDS STRESS AND INTONATION IN THE SECOND-SEMESTER PRONUNCIATION PRACTICE SUBJECT AT UPMI MEDAN - Nurhalimah, Nurhalimah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research discusses identifying students' ability to pronounce words by using three degrees of stress and three types of intonation, wherein these two categories, the results of students' abilities will be tested and the research uses quantitative research, which underlies percentage research using the Arikunto formula, namely: P = x 100%. It is known that the total number of students who pronounce in stress degrees can be found at 5,72 % is means that this score level is “less”, and the total number for the test by using intonation types is found 6% means “enough” for the score level.